A COMPARISON OF ANTIOXIDANT ACTIVITY IN TEA MISTLETOE (Scurrula atropurpurea (Bl.) Dans.) LEAF EXTRACTS USING DPPH ASSAY - Forrela Zahwa Salamah; Nour Athiroh Abdoes Sjakoer; Majida Ramadhan (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The general public often regards mistletoe as a parasitic plant that can harm other plants. However, some communities aware of its benefits have utilized mistletoe as an alternative treatment for various diseases. Tea mistletoe (Scurrula atropurpurea (Bl.) Dans.) is one type of mistletoe that the community has used to treat various ailments. Based on phytochemical analysis, this plant contains active compounds such as flavonoids, alkaloids, steroids, tannins, saponins, phenolics, and glycosides, which act as antioxidants. Therefore, this study was conducted to provide new information about the potential of tea mistletoe (Scurrula atropurpurea (Bl.) Dans.) leaf extract as a natural antioxidant with low toxicity effects through the DPPH method and to demonstrate the effectiveness of this natural antioxidant in inhibiting free radicals. This research is an experimental laboratory study with a quantitative approach. A series of sample concentrations was prepared, with 0,15 mL of each concentration placed into a 12-well plate and homogenized with 2,85 mL of 0,1 mM DPPH solution. The mixture was incubated for 30 minutes before its absorbance was measured using a UV-Visible Spectrophotometer. The results of this study showed that tea mistletoe (Scurrula atropurpurea (Bl.) Dans.) leaf extract exhibited very strong antioxidant activity, with an IC50 value of 3,32 ppm, comparable to quercetin. Keywords: tea mistletoe, DPPH, antioxidant, extract.